2003
DOI: 10.1254/jphs.91.145
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Negative c-Jun Inhibits Platelet-Derived Growth Factor-Directed Migration by Vascular Smooth Muscle Cells

Abstract: The mitogen-activated protein (MAP) kinase pathways has been shown to be necessary for mitogen-stimulated proliferation, but its role in cell migration has not been fully understood. In this study, we investigated the possible contribution of signaling pathways through c-Jun in platelet-derived growth factor (PDGF)-BB directed cell migration in rat aortic vascular smooth muscle cells (VSMCs) infected with a recombinant adenovirus containing the dominant-negative c-Jun (Ad-DN-c-Jun). DN-c-Jun protein was expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…The effects of platonin on c-Jun phosphorylation and p27 expression in PDGF-BB-stimulated VSMCs Several lines of evidence indicate that the JNK-mediated phosphorylation of c-Jun is necessary for cell proliferation [20,21] . Zhan et al [22] also reported that the pivotal role of c-Jun in PDGF-BB-induced VSMC proliferation is mediated by the down-regulation of p27 expression, an inhibitor of cyclindependent kinase (CDK).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of platonin on c-Jun phosphorylation and p27 expression in PDGF-BB-stimulated VSMCs Several lines of evidence indicate that the JNK-mediated phosphorylation of c-Jun is necessary for cell proliferation [20,21] . Zhan et al [22] also reported that the pivotal role of c-Jun in PDGF-BB-induced VSMC proliferation is mediated by the down-regulation of p27 expression, an inhibitor of cyclindependent kinase (CDK).…”
Section: Resultsmentioning
confidence: 99%
“…Activated JNKs result in the phosphorylation of many transcription factors, including the c-Jun component of the activator protein (AP)-1 transcription family [26,27] . c-Jun is known to be required for PDGF-induced VSMC migration and proliferation, and JNK knockdown can attenuate cell migration and proliferation in PDGF-stimulated VSMCs [20,22] . Furthermore, dominant-negative c-Jun lacking the transactivation domain of wild-type c-Jun (Ad-DN-cJun), which specifically blocks AP-1 transcriptional activity, significantly inhibited PDGF-BB-induced VSMC proliferation and suppressed PDGF-BB-induced down-regulation of CDK p27 [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, JNK may mediate Ang II-induced VSMC migration through c-Jun phosphorylation, because c-Jun as well as JNK is required for VSMC migration in response to PDGF. 39,8 Also, because the ERK cascade activation operated through EGFR transactivation is required for Ang II-induced VSMC migration, 40 it is likely that parallel ERK cascade activation together with the JNK cascade activation coordinately induce the migratory responses in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…85 Protein kinase C, proline-rich tyrosine kinase-2 (PYK2), and Rho/ROCK were found to be upstream of JNK activation and cell migration, but the downstream targets of JNK are less clear. C-Jun has been reported to be necessary for PDGF-induced VSM migration, 136 but how this protein affects migration is unknown. JNK can phosphorylate microtubule-associated proteins and paxillin.…”
Section: Mitogen-activated Protein Kinasesmentioning
confidence: 99%